Mini-review: Utilization of Vibrio parahaemolyticus virulence coding genes for early detection of acute hepatopancreatic necrosis disease (AHPND) - Yuhana, Munti; Afiff, Usamah (Jurnal Akuakultur Indonesia, 2023)
The ability to track the presence of pathogenic Vibrio parahaemolyticus, an AHPND causative agent in shrimp is one of the keys to controlling this infectious disease. A reputable disease diagnosis is appreciated as the ability to track the pathogenic infection when the host abnormality is undetectable due to the low pathogenic cell concentration. This mini-review article discusses the selected virulence encoding genes as molecular markers and the steps of standard validation methods in the application for early detection of AHPND disease. The proper diagnosis method is crucial to prevent the spread of Vibriosis AHPND which significantly results in economic losses for shrimp farmers. In this early warning system, we need a molecular method available for quick detection by applying the tracking tools that can discriminate pathogenic V. parahaemolyticus AHPND strain. Several types of potential genes that can be developed into tracking devices for infectious Vibriosis are pathogenic genes encoding the virulence factor. Through several stages of testing the selected virulence encoding genes will be developed into molecular markers. The polymerase chain reaction method and several of its variants have been widely applied using selected molecular markers. Furthermore, the use of molecular markers for the diagnosis of AHPND disease in shrimp must be validated by determining aspects of sensitivity, detection specificity, repeatability consistency, and reproducibility Keywords: virulence-encoding gene, Vibrio parahaemolyticus, AHPND, diagnose, molecular marker ABSTRAK Kemampuan melacak keberadaan patogen Vibrio parahaemolyticus, agen penyebab AHPND pada udang adalah salah satu kunci untuk mengendalikan penyakit menular ini. Diagnosis penyakit yang memiliki reputasi baik akan dihargai karena mampu untuk melacak infeksi patogen ketika tanda-tanda abnormalitas pada inang belum terdeteksi karena konsentrasi sel patogen yang masih rendah. Makalah mini-review ini membahas tentang tahap-tahap metode validasi standardalam aplikasi gen penyandi virulensi terseleksi untuk deteksi dini penyakit AHPND. Metode diagnosis yang tepat sangat penting untuk mencegah penyebaran Vibriosis AHPND yang secara signifikan mengakibatkan kerugian ekonomi bagi petambak udang. Dalam sistem peringatan dini ini, diperlukan metode molekular yang tersedia untuk deteksi cepat dengan menerapkan alat pelacak yang mampu membedakan patogen V. parahaemolyticus strain AHPND. Beberapa jenis gen potensial yang dapat dikembangkan menjadi alat pelacak penyakit Vibriosis menular adalah gen patogen yang mengkodekan faktor virulensi. Beberapa tahapan pengujian harus dilakukan untuk menjadikan gen penyandi virulensi terpilih sebagai kandidat yang akan dikembangkan menjadi penanda molekular. Metode polymerase chain reaction dan beberapa variannya telah banyak diterapkan dengan menggunakan penanda molekular terseleksi. Selanjutnya pemanfaatan penanda molekular untuk diagnosis penyakit AHPND pada udang harus dilakukan validasi dengan menentukan aspek sensitivitas, spesifisitas deteksi, konsistensi pengulangan, dan reprodusibilitas Kata Kunci: gen penyandi virulensi, Vibrio parahaemolyticus, AHPND, diagnosis, penanda molekuler